Phylogenetic and morphological diversity of free-living diplomonads - Mazancová, Eva; Zadrobílková, Eliška; Yubuki, Naoji; Čepička, Ivan (European journal of protistology, 2023)
Diplomonadida is a lineage of anaerobic protists belonging to Fornicata, Metamonada. Most diplomonads are endobiotic or parasitic, such as Giardia intestinalis, which is a famous human pathogen, but several free-living species exist as well. Although it has been proposed that the free-living diplomonads are descendants of endobiotic organisms and thus interesting from the evolutionary point of view, they have been largely neglected. We obtained 58 cultures of free-living diplomonads belonging to four genera (Hexamita, Trepomonas, Gyromonas, and Trimitus) and six strains of endobiotic diplomonads and analyzed their SSU rRNA gene sequences. We also studied light-microscopic morphology of selected strains and the ultrastructure of Trepomonas rotans for the first time. Our phylogenetic analysis showed that the genus Hexamita, and, possibly, also the genus Trepomonas, are polyphyletic. Trepomonas rotans, which may represent a novel genus, is unique among Diplomonadida by having the cell covered in scales. Our results suggest that the evolution of the endobiotic life style and cell organization in diplomonads is more complicated than previously thought.
Keywords: Hexamita; Diplomonadida; Humans; lidé; Phylogeny; Eukaryota; fylogeneze; Trepomonas; Ultrastructure